Constitutional Court Decisions and Substantive Justice Based on Islamic Values in the Pancasila State - Burhanuddin, Burhanuddin; Yandy, Eza Tri (Decisio: Journal of Judicial Law and Procedure, 2026)
This article examines the evolving role of the Indonesian Constitutional Court (Mahkamah Konstitusi, MK) in advancing substantive justice through constitutional adjudication grounded in Pancasila and informed by moral and religious values, particularly Islamic ethical reasoning. Departing from rigid legal formalism, the Court’s recent jurisprudence demonstrates an increasing reliance on principles of justice, humanity, proportionality, and public morality in interpreting constitutional norms. Employing a normative juridical research method with a conceptual and case-based approach, this study analyzes Constitutional Court Decision No. 97/PUU-XIV/2016 concerning the recognition of indigenous belief systems and Decision No. 24/PUU-XV/2017 on the constitutional right to religious education as primary legal materials. These decisions are examined in light of constitutional theory, comparative constitutionalism, and Islamic legal philosophy. The findings reveal that the MK no longer functions merely as a negative legislator that annuls unconstitutional statutes, but increasingly acts as a constitutional moral reasoner that actively shapes constitutional meaning. Islamic values, particularly those reflected in maqāṣid al-sharī‘ah, are not applied as formal sources of positive law but operate as ethical and normative references that enrich substantive justice within a Pancasila-based legal order. This integrative approach enables the harmonization of constitutionalism, moral reasoning, and religious values without undermining legal certainty, pluralism, or democratic governance. The article argues that Indonesian constitutionalism represents a distinctive model of value-based constitutional adjudication, offering a significant theoretical contribution to global constitutional discourse in plural societies.